E-Commerce as a Strategic Digital Capability for Sustainable MSME Performance: Evidence from Malaysia’s Insurance Sector - Loo, Mei Kay; Ramachandran, Sridar; Yusof, Raja Nerina Raja (Indonesian Journal of Sustainability Accounting and Management, 2026)
This study investigates the role of e-commerce as a strategic digital capability that supports the sustainable performance of Micro, Small, and Medium Enterprises (MSMEs) within Malaysia’s insurance sector. Drawing on the Technology Acceptance Model (TAM) and the Resource-Based View (RBV), the study examines how perceived usefulness, perceived ease of use, and perceived privacy influence the development of digital capability through e-commerce utilization. Data were collected from 276 MSME owners and managers in the Klang Valley and analyzed using Partial Least Squares Structural Equation Modeling. The results show that perceived usefulness, perceived ease of use, and perceived privacy significantly influence the utilization of e-commerce platforms. In turn, e-commerce utilization positively affects sustainable MSME performance. The mediation analysis further indicates that e-commerce utilization acts as an important mechanism through which managerial perceptions of digital technologies translate into long-term organizational resilience and competitive sustainability. These findings suggest that e-commerce should be viewed not merely as a technological tool but as a strategic capability that strengthens operational continuity, governance reliability, and long-term value creation. The study contributes to the sustainability accounting and management literature by providing empirical evidence from Malaysia’s MSME insurance sector and highlighting the importance of digital capability development for sustaining enterprise competitiveness in emerging economies.